Emergency Department Screening for Unhealthy Alcohol and Drug Use with a Brief Tablet-Based Questionnaire - Joshua W. Elder; Evan F. Wu; James A. Chenoweth; James F. Holmes; Aman K. Parikh; Aimee K. Moulin; Tommie G. Trevino; John R. Richards (Emergency Medicine International)
Background. Screening for unhealthy alcohol and drug use in the emergency department (ED) can be challenging due to crowding, lack of privacy, and overburdened staff. The objectives of this study were to determine the feasibility and utility of a brief tablet-based screening method in the ED and if patients would consider a face-to-face meeting with a certified alcohol and drug counselor (CADC) for more in-depth screening, brief intervention, and referral to treatment (SBIRT) helpful via this interface. Methods. A tablet-based questionnaire was offered to 500 patients. Inclusion criteria were age ≥18, Emergency Severity Index 2–5, and English comprehension. Subjects were excluded if they had evidence of acute intoxication and/or received sedating medication. Results. A total of 283 (57%) subjects were enrolled over a 4-week period, which represented an increase of 183% over the monthly average of patients referred for SBIRT by the CADC prior to the study. There were 131 (46%) who screened positive for unhealthy alcohol and drug use, with 51 (39%) and 37 (28%) who screened positive for solely unhealthy alcohol use and drug use/drug use disorders, respectively. There were 43 (33%) who screened positive for combined unhealthy alcohol and drug use. Despite willingness to participate in the tablet-based questionnaire, only 20 (15%) with a positive screen indicated via the tablet that a face-to-face meeting with the CADC for further SBIRT would be helpful. Conclusion. Brief tablet-based screening for unhealthy alcohol and drug use in the ED was an effective method to increase the number of adult patients identified than solely by their treating clinicians. However, only a minority of subjects screening positive using this interface believed a face-to-face meeting with the CADC for further SBIRT would be helpful.